Alpha-mangostin (Garcinia mangostana Linn.) and its potential application in mitigating chronic wound healing - Melonney Patrick,; Wan Najwa Wan Mohd Zohdi,; Suhaila Abd Muid,; Effat Omar, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Wound healing is a complex and dynamic cellular process to restore tissue function. Current treatments for chronic wounds especially diabetic ulcers are expensive, with adverse effects. Recently, numerous researchers have focused on the potential effect of natural products on wound healing. One of them is mangosteen (Garcinia mangostana Linn). It is a well-known tropical fruit that is native to Southeast Asia. The active ingredient of mangosteen pericarp contains xanthones that exhibit a wide range of pharmacological activities, including anti-inflammatory and anti-bacterial properties which are the core elements needed in wound healing. Firstly, this review discusses the concepts of abnormal and normal wound healing mechanisms. Then an in-depth observation of the pharmacological activities of mangosteen and its derivatives was presented to study their potentially beneficial applications in the treatment of chronic wound healing which is a contemporary medical issue.